2024
DOI: 10.3390/ma17040871
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Structural Properties in NiCo2O4/CuFe2O4 Bilayer Heterostructures on (001)-MgAl2O4 Substrate Regulated by Film Thickness

Kun Liu,
Ruyi Zhang,
Jiankang Li
et al.

Abstract: Changing film thickness to manipulate microstructural properties has been considered as a potential method in practical application. Here, we report that atomic-scale structural properties are regulated by film thickness in an NiCO2O4(NCO)/CuFe2O4(CFO) bilayer heterostructure prepared on (001)-MgAl2O4 (MAO) substrate by means of aberration-corrected scanning transmission electron microscopy (STEM). The misfit dislocations at the NCO/CFO interface and antiphase boundaries (APBs) bound to dislocations within the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This represents the most common approach used for altering the strain at the interface between the epitaxial film and the substrate and the resulting magnetic and electric properties [ 27 , 28 ]. Interfacial effects such as epitaxial strain [ 29 ], interface quality (i.e., defect, roughness, sharpness) [ 30 , 31 , 32 ], interdiffusion, and chemical intermixing [ 33 , 34 ] in multiferroic heterostructures have attracted tremendous attention for tuning and understanding the structure–property relationships as they allow one to control the magnetic interaction [ 35 ], spin ordering [ 36 , 37 ], and coupling across heterointerfaces, including ferromagnetic (FM)/antiferromagnetic (AFM) bilayer systems [ 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Several studies reported the occurrence of an exchange interaction based on the exchange bias (EB) at the interface of FM/AFM heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…This represents the most common approach used for altering the strain at the interface between the epitaxial film and the substrate and the resulting magnetic and electric properties [ 27 , 28 ]. Interfacial effects such as epitaxial strain [ 29 ], interface quality (i.e., defect, roughness, sharpness) [ 30 , 31 , 32 ], interdiffusion, and chemical intermixing [ 33 , 34 ] in multiferroic heterostructures have attracted tremendous attention for tuning and understanding the structure–property relationships as they allow one to control the magnetic interaction [ 35 ], spin ordering [ 36 , 37 ], and coupling across heterointerfaces, including ferromagnetic (FM)/antiferromagnetic (AFM) bilayer systems [ 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Several studies reported the occurrence of an exchange interaction based on the exchange bias (EB) at the interface of FM/AFM heterostructures.…”
Section: Introductionmentioning
confidence: 99%